Adherence to Lung-Protective Ventilation Principles in Pediatric Acute Respiratory Distress Syndrome: A Pediatric Acute Respiratory Distress Syndrome Incidence and Epidemiology Study*. Issue 10 (October 2021) - Bhalla, Anoopindar K.; Klein, Margaret J.; Emeriaud, Guillaume; Lopez-Fernandez, Yolanda M.; Napolitano, Natalie; Fernandez, Analia; Al-Subu, Awni M.; Gedeit, Rainer; Shein, Steven L.; Nofziger, Ryan; Hsing, Deyin Doreen; Briassoulis, George; et al.
Abstract : OBJECTIVES: To describe mechanical ventilation management and factors associated with nonadherence to lung-protective ventilation principles in pediatric acute respiratory distress syndrome. DESIGN: A planned ancillary study to a prospective international observational study. Mechanical ventilation management (every 6 hr measurements) during pediatric acute respiratory distress syndrome days 0–3 was described and compared with Pediatric Acute Lung Injury Consensus Conference tidal volume recommendations (< 7 mL/kg in children with impaired respiratory system compliance, < 9 mL/kg in all other children) and the Acute Respiratory Distress Syndrome Network lower positive end-expiratory pressure/higher FIO2 grid recommendations. SETTING: Seventy-one international PICUs. PATIENTS: Children with pediatric acute respiratory distress syndrome. INTERVENTIONS: None. MEASUREMENTS AND MAIN RESULTS: Analyses included 422 children. On pediatric acute respiratory distress syndrome day 0, median tidal volume was 7.6 mL/kg (interquartile range, 6.3–8.9 mL/kg) and did not differ by pediatric acute respiratory distress syndrome severity. Plateau pressure was not recorded in 97% of measurements. Using delta pressure (peak inspiratory pressure – positive end-expiratory pressure), median tidal volume increased over quartiles of median delta pressure ( p = 0.007). Median delta pressure was greater than or equal to 18 cm H2 O for all pediatric acute respiratory distress syndrome severity levels. In severe pediatric acute respiratory distress syndrome, tidal volume was greater than or equal to 7 mL/kg 62% of the time, and positive end-expiratory pressure was lower than recommended by the positive end-expiratory pressure/FIO2 grid 70% of the time. In multivariable analysis, tidal volume nonadherence was more common with severe pediatric acute respiratory distress syndrome, fewer PICU admissions/yr, non-European PICUs, higher delta pressure, corticosteroid use, and pressure control mode. Adherence was associated with underweight stature and cuffed endotracheal tubes. In multivariable analysis, positive end-expiratory pressure/FIO2 grid nonadherence was more common with higher pediatric acute respiratory distress syndrome severity, ventilator decisions made primarily by the attending physician, pre-ICU cardiopulmonary resuscitation, underweight stature, and age less than 2 years. Adherence was associated with respiratory therapist involvement in ventilator management and longer time from pediatric acute respiratory distress syndrome diagnosis. Higher nonadherence to tidal volume and positive end-expiratory pressure recommendations were independently associated with higher mortality and longer duration of ventilation after adjustment for confounding variables. In stratified analyses, these associations were primarily influenced by children with severe pediatric acute respiratory distress syndrome. CONCLUSIONS: Nonadherence to lung-protective ventilation principles is common in pediatric acute respiratory distress syndrome and may impact outcome. Modifiable factors exist that may improve adherence. Abstract : Supplemental Digital Content is available in the text.